Discussion around the Francoise Mayer´s Book "The Czechs and Their Communism": Pro koho by měla být vysokoškolská výuka historie - Blaive, Muriel (Dějiny – teorie – kritika, 2024)
This discussion contribution focuses on three questions inspired by Francoise Mayer´s book. Was the Velvet Revolution really a revolution (and hence: is the Czech exception in Central Europe really an exception?); what can the sociologist do when the historians have not yet done their job?; and can one forget genuine reality, i.e. socio-economic history? The contribution aimed to stress that despite the considerable quality and usefulness of Mayer´s book, any kind of sociology of post-communist society will remain inadequate unless backed by sufficient research in the field of the social history of communist and specifically here the relationship of Czech society to communism. One secondary and negative effect of the lack of such studies is the tendency for current debate (fascinating but rather irrelevant and generally very provincial) on Czech collective memory of the period of communism to concentrate on the question of Czech character or on the question of the "mission" of the Czech historian. But arguably the historian is more useful when actually doing research than when endlessly reflecting on his own character.